The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3897/zookeys.147.2047
|View full text |Cite
|
Sign up to set email alerts
|

Carabidae diversity along an altitudinal gradient in a Peruvian cloud forest (Coleoptera)

Abstract: Carabid beetles were sampled at five sites, ranging from 1500 m to 3400 m, along a 15 km transect in the cloud forest of Manu National Park, Perú. Seasonal collections during a one year period yielded 77 morphospecies, of which 60% are projected to be undescribed species. There was a significant negative correlation between species richness and altitude, with the number of carabid species declining at the rate of one species for each 100 m increase in altitude. The majority of species (70.1 %) were restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 35 publications
(45 reference statements)
3
26
1
8
Order By: Relevance
“…This result is in agreement with carabid species richness patterns investigated in other mountain areas (e.g. Maveety, Browne, & Erwin, ; Winkler et al, ; Zou, Sang, Zhou, Huang, & Axmacher, ). Our results highlighted that the studied species traits (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…This result is in agreement with carabid species richness patterns investigated in other mountain areas (e.g. Maveety, Browne, & Erwin, ; Winkler et al, ; Zou, Sang, Zhou, Huang, & Axmacher, ). Our results highlighted that the studied species traits (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Recent evidence suggests that the most common elevational pattern is the increase of diversity and species richness at intermediate elevations (Rahbek 2005, McCain and Grytnes 2010, Sanders and Rahbek 2012, Guo et al 2013), which has been documented for various groups of Coleoptera (Escobar et al 2005, Fernández et al 2010), including Chrysomelidae (Furth 2009, Sánchez-Reyes et al 2014). Other studies have shown a decrease of species richness with increasing elevation for various groups of insects (Wolda 1987, McCoy 1990, Sánchez-Ramos et al 1993, Araújo and Fernandes 2003, Maveety et al 2011, Jones et al 2012). Indeed, it has been observed that species richness, abundance and diversity of Lepidoptera decreases with increasing elevation in Cerro El Diente (Meléndez-Jaramillo et al 2015), which is one of the sampling localities in our study.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the proved ecological relevance of GB, problems in species identification and the lack of systematic natural history studies might originate constraints for their practical use as surrogates in routine ecological studies (Freitas et al, 2006). However, in our study most of the RTU were identified until the level of morphospecies (Maveety et al, 2011). We realize that this is a simplified, preliminary and demonstrative approach, although we believe that RTU classification represents a reasonable trade-off between absolute taxonomic accuracy (which may take many years to achieve) and the ecological functional representativeness, necessary to ensure the applicability of GB diversity estimates for comparative analysis between different ecosystems (Maveety et al, 2014).…”
Section: Perspectives and Challenges On Using Neotropical Ground Beetmentioning
confidence: 96%